Upaya Penanggulangan Anak Jalanan Oleh Dinas Sosial Kota Ambon - Selvyana Warwuru; Sherly Adam; Ronald Saija (PATTIMURA Law Study Review, 2023)
Every child has the right to live, grow, develop and participate reasonably in accordance with the dignity of humanity, and receive protection from violence and discrimination and the Government is obliged to organize the maintenance and care of neglected children, both in institutions and outside institutions. This study aims to determine how the efforts and role of the Ambon City Social Service in overcoming Street Children in Ambon City.The research method used with empirical juridical research type. data collection techniques are observation, interviews and documentation. Legal materials used are primary legal materials and secondary legal materials. The data that has been collected is then analyzed through description using qualitative methods.The results showed that the role of the Ambon City Social Service for street children in Ambon City is as a parent, as a teacher and also as a supervisor and the countermeasures made by the Ambon City Social Service itself against street children are raids and street child screening, Social Guidance for families of street children, and providing nutritional assistance. In the efforts to overcome street children in Ambon City, the Ambon City Social Service is still classified as ineffective in tackling the problem of street children because there are no strict sanctions for parents of street children or certain individuals. To improve efforts to deal with street children, the Ambon City Social Service really needs a Halfway House to accommodate these street children.